High-throughput quantitation method for amodiaquine and desethylamodiaquine in plasma using supported liquid extraction technology - Kaewkhao, K; Tarning, J; Blessborn, D (Elsevier, 2021)
Amodiaquine is a drug used for treatment of malaria and is often used in combination with artesunate in areas where malaria parasites are still susceptible to amodiaquine. Liquid chromatography tandem-mass spectrometry was used to quantify amodiaquine and its active metabolite, desethylamodiaquine, in plasma samples. A low sample volume of 100 µl, and high-throughput extraction technique using a supported liquid extraction (SLE+) technique on an automated liquid handler platform for faster sample processing are some of the advantages of this method. Separation of amodiaquine from desethylamodiaquine was achieved using a reversed phase Zorbax SB-CN 50 mm × 4.6 mm, I.D. 3.5 µm column with acetonitrile and 20 mM ammonium formate with 1% formic acid pH ~ 2.6 (15–85, v/v) as mobile phase. The absolute recoveries of amodiaquine and desethylamodiaquine were 66% to 76%, and their isotope label internal standard were in the range of 73% to 85%. Validation results of the developed method demonstrated intra-batch and inter-batch precisions within the acceptance criteria range of ± 15.0%. There were no matrix or carry-over effects observed. The lower limit of quantification was 1.08 ng/ml for amodiaquine and 1.41 ng/ml for desethylamodiaquine. The method showed robust and accurate performance with high sensitivity. Thus, the validated method was successfully implemented and applied in the evaluation of a clinical trial where participants received artemether–lumefantrine plus amodiaquine twice daily for three days (amodiaquine dose of 10 mg base/kg/day).